Assessment of community-based intervention approaches to improve the health and welfare of working donkeys in selected areas of Sidama region, Southern Ethiopia - Yalew, Aweke; Darge, Daniel; Melake, Berhanu Mekibib (Frontiers in Veterinary Science, 2024)
Background: Although effort has been made by certain non-governmental organizations, like the Donkey Sanctuary, SPANA (Society for the Protection of Animals Abroad) and Brooke Ethiopia, to change the attitude and practice of the donkey owners towards improving the health and welfare working donkeys, their impact has not been assessed so far. A cross-sectional study was hence conducted to assess and compare donkeys' health and welfare problems in the community based intervention areas versus non-intervention areas in selected districts of Sidama regional state, Southern Ethiopia.For the animal based welfare assessments, 200 donkeys each were selected and included from intervention and non intervention areas. The selected donkeys were then assessed for their welfare and health status using 5 important parameters; namely body condition score, presence and severity of wounds, behavior, presence and severity of lameness, and presence of other signs of illness/diseases.The prevalence and severity of lameness and wounds on donkeys managed in nonintervention areas were higher than the ones observed in the community based intervention areas. The prevalence of lameness in the non-intervention areas (25.5%) was over two fold compared to the prevalence in the intervention areas (12%). Likewise, over 37% of the donkeys in the nonintervention areas were wounded, of which 64% were suffering with moderate to severe wounds. Moreover, donkeys in the intervention areas were with better body condition, alert and friendly to human approach. There was statistically significant difference (p< 0.01) between the intervention and non intervention areas in all the considered parameters, namely the presence of lameness, wound, body condition score, demeanor and response to approach.Based on the current finding, the community based intervention approach was found to improve the health and welfare of working donkeys. Therefore, a comprehensive and continuous equine health and welfare promotion through community based intervention approaches should be designed and implemented to improve the welfare of working equines in the country.